EFFECT OF FOLIAR APPLICATION OF MAXI-GROW AND POTASSIUM ON GROWTH, YIELD AND NUTRIENT CONTENT OF LETTUCE (LACTUCA SATIVA L.) UNDER PLASTIC HOUSE CONDITION - SAEID, ABDULJEBBAR I.; F, SUHAILA RAFEEQ; D, OMEED MOHAMMAD; ASWAD, SAAD YOUSF (Journal of Duhok University, 2023)
The research was carried out in a plastic house at the Malta station  research  farm in Duhok, kurdistan region/ Iraq. In the autumn 2019 growing season to study the influence  of foliar spraying by seaweed extract (Max grow) with concentrations of  (0, 3, 6, and 9 ml.l-1) and potassium( 0, 1.5 and 3 g.l-1 )on lettuce teresa on vegetative  growth, yield  and its chemical content in leaves. The application of seaweed extract and potassium was done 10 days after transplanting and repeated 3 time in interval 10 days. Result should that seaweed extract significantly increased (head weight, head diameter, leaf width, dry weight, N,P,K and Yields). Also, potassium gave the highest value and significantly increased head diameter, leaf width, dry weight, Ca concentration. However, the interactions between two factors significantly increased all the parameters where studied compared with control